Upaya Meningkatkan Kreativitas Anak Melalui Permainan Puzzle Di TK Satap Sibargot Tahun Pelajaran 2022/2023 - Ihdania Rambe; Muhammad Zulham Munthe (Cemara Education and Science, 2024)
This research aims to evaluate and increase the creativity of young children through the implementation of puzzle games at the Satap Sibargot Kindergarten (TK) in the 2022/2023 academic year. The research method used was classroom action research with participants totaling 30 children aged 4-5 years. The research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection. In the first cycle, puzzle games were introduced as a learning medium to increase children's creativity. Observation results show an increase in children's interest and participation in puzzle activities. In the second cycle, the puzzle game is adapted to the child's level of cognitive complexity and variations in theme, taking into account individual preferences. Observations showed significant improvements in children's problem-solving abilities and creative expression. The findings of this research confirm that implementing puzzle games can be an effective strategy in increasing children's creativity in kindergarten. The practical implications of this research include recommendations for curriculum development and teacher training so that they can make optimal use of puzzle games as a means of creative learning for young children. Further research is also recommended to explore the long-term impact of efforts to increase children's creativity through puzzle games in formal education environments.